CD69 expression in regulatory T cells protects from the immune-mediated damage after myocardial infarction. (14th October 2021) - Blanco-Dominguez, R; De La Fuente, H; Garcia-Guimaraes, M M; Rodriguez, C; Rodriguez-Arabaolaza, I; Jimenez-Alejandre, R; Sanchez-Diaz, R; Alfonso, F; Sanchez-Madrid, F; Martinez-Gonzalez, J; Martin, P
Abstract:  : CD69 depletion from the lymphoid compartment promotes a Th17/Treg imbalance and exacerbates the development of atherosclerosis. As atherosclerosis is the trigger of myocardial infarction, we have analyzed the role of CD69 in Treg cells after a) permanent occlusion of the left-anterior-descending coronary artery (LAD-ligation) in mice, and b) coronary angiography in two cohorts of acute myocardial infarction (MI) patients. Our data show that CD69 expression in Treg cells is critical to maintain immune homeostasis after myocardial infarction and increases overall survival in mice after LAD-ligation. Cd69−/− mice develop IL17A+ gdT cell responses early after ischemia that increment myocardial inflammation and, consequently, worsen cardiac function. Furthermore, we found that CD69+ Treg cells induce apoptosis and diminish IL-17A production in gdT cells by a mechanism dependent on membrane CD39 ectonucleotidase activity. The adoptive transfer of CD69+ Treg cells to Cd69−/− mice after LAD-ligation reduces IL17A+ gdT cell recruitment, resulting in increased survival and improved outcome. In accordance, data from two independent cohorts of patients indicate that increased levels of CD69+ Treg cells in the blood of patients early after MI is associated with lower risk of developing chronic heart failure. Our data support the role of CD69+ Treg cells to prevent excess of inflammation and damage after MI, whose value remains associated with improved heart function in the medium term. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Fondo de Investigaciones Sanitarias. Instituto de Salud Carlos III. Ministerio de Ciencia Innovaciόn y Universidades (Spanish Government).